APPROACH TO DETECTION OF FACE OCCLUSION IN ACCESS CONTROL SYSTEMS (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes methods for detecting face masks in access control and management systems, and also presents a method of convolution neural networks for detecting face masks using deep machine learning technology. Face mask images in the form of a neural network model were trained on the generated database, and performance metrics were determined using metrics such as model accuracy, F1-score, precision and recall.